2012
DOI: 10.1002/art.34456
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral disc and macrophage interaction induces mechanical hyperalgesia and cytokine production in a herniated disc model in rats

Abstract: Objective. The expression of proinflammatory factors such as tumor necrosis factor ␣ (TNF␣), interleukin-6 (IL-6), IL-8, and prostaglandin E 2 (PGE 2 ) is significantly correlated with the symptoms of herniated disc disease. Among the different types of immune cells, macrophages are frequently noted in the herniated disc tissue. We undertook this study to clarify the interaction of the intervertebral disc (IVD) and macrophages with regard to the production of TNF␣, IL-6, IL-8, and PGE 2 .Methods. We developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 50 publications
6
66
1
2
Order By: Relevance
“…An increase in expression of some cytokines and MMPs in herniated IVD may occur when molecules seen as 'non-self' by immune cells become exposed. This may also be linked to the phenomenon of spontaneous regression or disappearance of extruded IVD fragments, which has been attributed to matrix degradation and phagocytosis by recruited/infiltrated macrophages [102][103][104][105][106]. In cases with transligamentous extrusion, which can occur when the NP is potentially more exposed to immune cells, regression occurs [107].…”
Section: Mmp19mentioning
confidence: 99%
“…An increase in expression of some cytokines and MMPs in herniated IVD may occur when molecules seen as 'non-self' by immune cells become exposed. This may also be linked to the phenomenon of spontaneous regression or disappearance of extruded IVD fragments, which has been attributed to matrix degradation and phagocytosis by recruited/infiltrated macrophages [102][103][104][105][106]. In cases with transligamentous extrusion, which can occur when the NP is potentially more exposed to immune cells, regression occurs [107].…”
Section: Mmp19mentioning
confidence: 99%
“…10,32,65 An in vitro study that investigated the ability of HA and the polysulfated polysaccharide pentosan polysulfate (PPS) to promote chondrogenic differentiation of MPCs in culture found that HA over a concentration range of 2.5-20 m/ml inhibited MPC chondrogenesis rather than promoted it. 19 In contrast, PPS markedly stimulated MPC chondrogenic differentiation and also promoted cell proliferation, reduced MPC apoptosis, and inhibited osteogenic differentiation.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that when the IVD was relocated in vivo, the autografts induced TNF-α and IL-1β mRNA upregulation, rapidly followed by macrophage infiltration (25). The phosphorylation of p38 MAPK, an important component of the MAPK family, was closely associated with the secretion and accumulation of proinflammatory factors.…”
Section: Discussionmentioning
confidence: 99%